HUBUNGAN PERSONAL HYGIENE SAAT MENSTRUASI DENGAN KEJADIAN PRURITUS VULVAE PADA REMAJA DI SMA NEGERI 7 MANADO - Pandelaki, Lingkan G. E. K.; Rompas, Sefti; Bidjuni, Hendro (JURNAL KEPERAWATAN, 2020)
AbstrackBackground : Cleanliness of genetal areas (Personal Hygiene) especially when menstruation is often neglected by adolescents, if they do not maintain genetal hygiene properly, then in a moist condition, fungi and bacteria that are in the genetal area will flourish, causing itching (Pruritus Vulvae) and infection in the area. The purpose of this research was to determine the corelation between Personal Hygiene and the incidence of pruritus vulvae in adolescents in Public Senior High School 7 Manado. This research method used a descriptive analytic research design with Cross Sectional Study approach. A sample of 148 respondents were obtained using the Simple Rondom Sampling technique. The test results showed the relationship between Personal Hygiene During Menstruation with the incidence of Pruritus Vulvae with the incidence of pruritus vulvae in adolescents in the moderate category of 65 respondents (66.3%). The conclusion is that there is a relationship between Personal Hygiene and the incidence of pruritus vulvae in adolescents in Manado's 7th Middle School.Keywords: Personal Hygiene, Pruritus Vulvae, Menstruation.AbstrakLatar Belakang Kebersihan daerah genetalia (Personal Hygiene) terutama ketika menstruasi sering diabaikan oleh remaja, jika tidak menjaga kebersihan genetalia dengan benar, maka dalam keadaan lembab, jamur dan bakteri yang berada di daerah genetalia akan tumbuh subur sehingga menyebabkan rasa gatal (Pruritus Vulvae) dan infeksi pada daerah tersebut. Tujuan untuk mengetahui hubungan Personal Hygiene dengan Kejadian Pruritus Vulvae Pada Remaja di Sekolah Menengah Atas Negeri 7 Manado. Metode penelitian ini menggunakan desain penelitian yaitu Deskriptif Analitik dengan pendekatan Cross Sectional Study. Sampel berjumlah 148 responden yang didapat dengan menggunakan tehnik Simple Rondom Sampling. Hasil uji didapatkan hasil hubungan antara Personal Hygiene Saat Menstruasi dengan Kejadian Pruritus Vulvae dengan kejadian pruritus vulvae pada remaja dalam kategori sedang sebanyak 65 orang responden (66,3%).Kesimpulan ada hubungan antara Personal Hygiene dengan Kejadian Pruritus Vulvae Pada Remaja di Sekolah Menegah Atas Negeri 7 Manado.Kata kunci : Personal Hygiene, Pruritus Vulvae, Menstruasi.